Numerical analysis of natural convection in shed roofs with eave of buildings for cold climates - Koca, Ahmet; Öztop, Hakan Fehmi; Varol, Yasin (Pergamon-Elsevier Science Ltd, 2008)
A numerical study has been carried Out on partially heated triangular enclosures with eave. The eave and inclined wall has a cold temperature. The laminar, two-dimensional steady, governing equations of natural convection are solved in the streamfunction-vorticity form using a finite difference technique. Streamline, isotherm and number are presented for different parameters such as aspect ratio AR = H/L. from 0.25 to 1, ratio of eave length E = L/n where it changes from 3 to 7 and Rayleigh number from 10(3) to 10(6). It is observed that the heat transfer decreases with increasing aspect ratio for small Rayleigh number but increases for higher Rayleigh number. Heat transfer also increases with decreasing eave length. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Shed roof; Eave; Heat transfer; Laminar flow